Frank Riess, The word and the stone. Language and imagery in Neruda's "Canto general". Oxford University Press, Oxford, 1972; xviii + 170 pp. (Oxford modern languages and literature monographs). - Jacques Joset (Nueva Revista de Filología Hispánica, 1974)
Se reseñó el libro: The word and the stone. Language and imagery in Neruda's "Canto general".